PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK KELAS IV SEKOLAH DASAR - Indah Oktaviani; Zerri Rahman Hakim; Indhira Asih Vivi Yandari (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2023)
This research aims to determine the use of the problem based learning model on students' creative thinking abilities and to find out how much contribution arises from student responses in using the problem based learning model for Gempol State Elementary School students. The method used in this research is a quantitative method, with a quasi-experimental design with 26 respondents as subjects of class IV students. Based on the results of hypothesis testing using the t test, a calculated t value of 2.249 was obtained. From these results it is known that the calculated t value> t table, then H0 is rejected and Ha is accepted. Apart from that, the data for the average value of the control class is smaller than the average value of the experimental class. The control class average was 70.77 while the experimental class average was 76.73. So it can be concluded that the use of the Problem Based Learning learning model has an effect on the creative thinking abilities of class IV elementary school students.